Road to Tokyo 2020 Olympic Games: Training Characteristics of a World Class Male Triathlete - Cejuela, Roberto; Sellés-Pérez, Sergio (Frontiers in Physiology, 2022)
There is a growing interest in the scientific literature for reporting top-class endurance athletes training programs. This study reports on the training program of a world-class male triathlete preparing to compete in the Tokyo 2020 Olympic Games. A macrocycle of 43 weeks is presented. The triathlete performed 14.74  3.01 hours of weekly training volume. Training intensity distribution was 81.93  6.74 / 7.16  2.03 / 10.91  6.90 for zones 1,2 and 3 respectively. Polarized TID model is observed at the end of the macrocycle but pyramidal during the initial stages. The triathlete increased his VO2max 19.72% on cycling and 13.61% on running during the training program, as well as, maximum aerobic power was increased 3.13% on cycling and maximum aerobic speed 9.71% on running. Finally, the triathlete placed 12th in Olympic distance and 10st in Mixed Relay in Tokyo 2020 Olympic games.